2015
DOI: 10.4103/2277-9175.161585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Γ-aminobutyric acid on kidney injury induced by renal ischemia-reperfusion in male and female rats: Gender-related difference

Abstract: Background:The most important cause of kidney injury is renal ischemia/reperfusion injury (IRI), which is gender-related. This study was designed to investigate the protective role of Γ-aminobutyric acid (GABA (against IRI in male and female rats.Materials and Methods:Thirty-six female and male wistar rats were assigned to six experimental groups. The IRI was induced by clamping renal vessels for 45 min then was performed reperfusion for 24 h. The group sex posed to IRI were pretreated with GABA and were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…reported that GABA decreased the serum level of Cr in renal ischemic/reperfusion in female, but not in male rats. [ 30 ] In clinical medicine, the causes of acute kidney injury are often divided into prerenal, intra renal, and postrenal. The BUN/Cr ratio is used to distinguish prerenal dysfunction,[ 31 ] and it is also considered as a renal function indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that GABA decreased the serum level of Cr in renal ischemic/reperfusion in female, but not in male rats. [ 30 ] In clinical medicine, the causes of acute kidney injury are often divided into prerenal, intra renal, and postrenal. The BUN/Cr ratio is used to distinguish prerenal dysfunction,[ 31 ] and it is also considered as a renal function indicator.…”
Section: Discussionmentioning
confidence: 99%
“…reported,[ 44 ] while GABA in the form of prophylaxis and therapy, decreased UW, and this finding was in agreement with other documents. [ 30 ] MDA, as the final product of lipid peroxidation, is one of the biomarkers of oxidative stress. [ 45 ] CP administration is leading to lipid peroxidation and increase the MDA level.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the increases in alanine amino transferase and aspartate amino transferase activities, urea and creatinine levels, malondialdehyde and advanced oxidation protein levels, and oxidative damage to the kidney tissues induced by γ-irradiated- and streptozotocin-treated rats were markedly attenuated by Gaba administration in rats [122]. Especially, Gaba was observed to ameliorate kidney injury induced by renal ischemia/reperfusion injury in a gender dependent manner [123]. These results emphasized the protective effect of Gaba against the renal damage involving in renal failure.…”
Section: Pharmaceutical Properties Of Gabamentioning
confidence: 99%
“…In addition, the effect of GABA on renal I/R injury exhibited gender-related difference. GABA treatment can attenuate pathological renal parameters (blood creatinine and urea nitrogen, kidney weight, and renal level of malondialdehyde) in female rats rather than male rats [176]. However, it was intriguing that GABA was unable to protect renal I/R injury in ovariectomized rats whether estradiol was administrated or not [177].…”
Section: Roles Of Gaba In I/r Injuries Of Other Organs Outside Of mentioning
confidence: 99%